The Role of Auditory Attention in Shaping Immersive Experiences in Augmented Reality Museum Settings - Piao, Gui Cheng; Lee, Jun Choi; Rehman Ullah, Khan (Human Resource Management Academic Research Society (hrmars), 2025)
Abstract This study examines how auditory attention shapes immersive experiences in AR-enhanced museum exhibitions. While sound is integral to multisensory engagement, its specific influence in curatorial environments remains underexplored. Based on empirical data from an AR exhibition at a provincial museum in China, the findings show a significant positive relationship between auditory attention and immersion. Auditory cues were found to deepen both cognitive and emotional engagement. Framed by the Stimulus–Attention–Organism–Response (S-A-O-R) model, the study highlights sound’s role as an active agent in shaping immersive perception. These results contribute to emerging discussions on multisensory aesthetics and visitor-centered museum design. By bridging empirical analysis with a structuralist framework, this research offers new insights into how auditory elements can be strategically integrated into curatorial practices to enhance cultural experience. Keywords: Auditory Attention, Immersive Museum Experience, Augmented Reality (AR), Visitor Engagement, Cognitive Immersion